2013
DOI: 10.7763/joebm.2013.v1.83
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Fluctuations and Firm Performance in an Emerging Market: Assessing Volatility and Asymmetric Effect

Abstract: Abstract-This study examines the impact of oil price volatility on firm performance in the context of an emerging market, Malaysia. The effect of crude oil price on the performance is examined for the period of January 1986 to December 2011 using GARCH and EGARCH models reflecting the evaluation on volatility and asymmetric effects. Results indicate the significant effect of oil price volatility on stock market volatility and also the asymmetric effects. For policy makers, the findings help to clarify the dile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…In order to find accurate and real effects of GEPU, this study considers few macroeconomic variables, such as interest rate, 6 exchange rate, 7 and oil price, 8 as control variables, which also act as local/regional variables. These variables have shown significant influences on Malaysian stock performances (see, Janor, Abdul-Rahman, Housseinidoust, & Rahim, 2013;Nordin, Nordin, & Ismail, 2014).…”
Section: Data and Preliminary Analysismentioning
confidence: 99%
“…In order to find accurate and real effects of GEPU, this study considers few macroeconomic variables, such as interest rate, 6 exchange rate, 7 and oil price, 8 as control variables, which also act as local/regional variables. These variables have shown significant influences on Malaysian stock performances (see, Janor, Abdul-Rahman, Housseinidoust, & Rahim, 2013;Nordin, Nordin, & Ismail, 2014).…”
Section: Data and Preliminary Analysismentioning
confidence: 99%
“…With the decline in oil prices, there were negative effects on the stock returns. Using the GARCH and EGARCH models, Janor et al (2013) concluded that that oil price volatility had a significant effect on firms for the period from January 1986 to December 2011. Studying the same variables, Dadashi et al (2015) sampled firms listed on the Tehran Stock Exchange from 2003 to 2013 and concluded that oil prices significantly affected firm value based on Tobin's Q.…”
Section: Impact Of Oil Price On Profitability Performancementioning
confidence: 99%
“…The results conclude that the financial performance of the banks is similar in the precrisis and crisis period. Janor et al (2013) studied the relationship between the effects of oil prices and firm performance based on ROA ROE, leverage and other factors. Wattanatorn and Kanchanapoom (2012) measured the ratio of net profit to total equity.…”
Section: Impact Of Oil Price On Profitability Performancementioning
confidence: 99%
See 1 more Smart Citation
“…We use the KLCI Composite as a Malaysian stock market proxy. To fi nd accurate eff ects of GEPU, this study considers a few macroeconomic variables as control variables, such as interest rate (see Nordin et al, 2014), exchange rate (see Nordin et al, 2014), and oil price (Janor et al, 2013), which may have signifi cant impacts on stock market performance. It is worth noting that the monthly frequency data choice is directed by the availability of data on the Global Economic Policy Uncertainty index.…”
Section: Dataset Descriptionsmentioning
confidence: 99%